2016
DOI: 10.1021/acs.jpcc.5b12045
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of V Dopants in TiO2 Nanoparticles: X-ray Absorption Spectroscopy, Including Ab-Initio and Full Potential Simulations

Abstract: Doping with transition metals is an effective method to enhance visible light absorption in TiO2 nanoparticles and to improve the efficiency of many photocatalytic processes under solar radiation. A determination of the incorporation site of the dopant and an understanding of the local bonding arrangement and electronic structure is a necessary step for knowledge -based materials design. In this paper, we report an in-depth X-ray Absorption Spectroscopy study of V dopants in TiO2 nanoparticles deposited by gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
6
14
0
Order By: Relevance
“…stitutional V acts as a deep donor with the ε(+/0) transition level at 1.59 eV below the HSE CBM (or 1.37 eV below the experimental CBM). This result is in line with x-ray absorption spectroscopy results 55 and EPR measurements 56 which show that vanadium is in the charge state "V 4+ " (i.e. q = 0 in our notation), which confirms its deep character as an electron donor.…”
Section: Defect Formation Energiessupporting
confidence: 89%
“…stitutional V acts as a deep donor with the ε(+/0) transition level at 1.59 eV below the HSE CBM (or 1.37 eV below the experimental CBM). This result is in line with x-ray absorption spectroscopy results 55 and EPR measurements 56 which show that vanadium is in the charge state "V 4+ " (i.e. q = 0 in our notation), which confirms its deep character as an electron donor.…”
Section: Defect Formation Energiessupporting
confidence: 89%
“…HERFD-XAS can be used to study charge-transfer processes, as shown by the recent study by some of us of hot electron transfer from Au to TiO 2 NPs induced by plasmon excitation in the metal [9]. As for the specific system investigated, we have recently demonstrated that V dopants in TiO 2 NPs are found in both 4+ and 5+ oxidation states in bulk and surface sites, respectively, and occupy substitutional sites irrespective of whether the matrix has an atomic structure similar to rutile or anatase [10]. Now, we use V Kαand Ti Kβ-detected HERFD-XANES under differential illumination to demonstrate that visible light absorption predominantly leads to electron transfer from V to long-lived Ti-related traps.…”
Section: Introductionmentioning
confidence: 86%
“…%. Further information about the deposition procedure can be found in previous publications [43,45].…”
Section: Methodsmentioning
confidence: 99%
“…A previous electrochemical study showed that -NO2 reduction takes place at about 0.5 eV below the CBM [52]. Since sub-bandgap visible light cannot promote electronic transitions from the valence to the conduction band, the initial electron state must be an intra-gap state associated with V, which is incorporated as a substitutional V 4+ cation in the lattice of both rutile and anatase [43,44]. There is a significant spread in the calculated energy level of the electronic state localized on V 4+ , which was reported between 0.7 eV [16,20] and 1.36 eV [21] below the CBM.…”
Section: Correlation Between Charge Carrier Dynamics and Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation